The Interpretive Purposes of Surat Al-Kahf Stories (Journal of the College of Basic Education, 2024)
In this research, we dealt with the subject of (the interpretive purposes of the stories of Surat Al-Kahf), which was represented by three sections and an introduction. We were exposed in the first section of money (the story of the owner of the two gardens) The second topic was about science (the story of Al-Khidr and our master Moses, peace be upon them) dealt with the Quranic verses that concern science in Surat Al-Kahf .The third section was about power (the story of Dhul-Qarnayn) and then the conclusion and followed by sources references